Estudo da transferência de calor em painel fotovoltaico - Santandrea, Priscila Medeiros (2019)
The use of renewable energy is the way to sustainable development. Brazil has stood out in the world scene because of the long tradition in the use of renewable sources, such as hydroelectric power and biomass. More recently, Rio Grande do Norte has become the largest national producer of renewable energy from the winds. This study is the state of potential of solar energy, even incipient this sector. For this pretension to be made feasible, technically and economically, studies are necessary that consider as regional and local peculiarities. In this sense, it is necessary to use photovoltaic panels. Due to the high solar radiation, there is an overheating of the panels, which reduce the efficiency of solar radiation and reduce the shelf life of photovoltaic cells. Aiming at helping to obtain the use of solar energy in the RN, considering the possibility of reducing the consumption of solar energy through passive cooling. Thus, no work was done, an experimental study was carried out in which a photovoltaic panel was moderated in two situations: with and without heat exchange between the panel and a water container. For warming the panel temperature, there were three different working fluids: air, water and ethylene glycol. The experiments were carried out in a thermally controlled environment, with the heat of a bank of incandescent batteries and the temperature monitoring by means of thermocouples coupled to a computer data capture system. For each fluid, three experiments were used. Reference was made to the condition of the carrier coupled to the base of the air-contained panel. In this case, as expected, they were the highest values for the panel average. When shipping was done with water, the heat was below 2 ° C below the previous case. The result was when filling the container with ethylene glycol.